Consequencialismo judicial e eficiência: uma perspectiva ética - Nunes, Miguel Cordeiro (2020)
Excessive judicialization has induced the production of judicial decisions which are not always balanced, since, despite having in many cases solved concrete disputes between the parties, such decisions have resulted in detrimental economic, social and political effects that often have a great impact and that were not considered at the moment of the rendition of the judgment. Various have been the examples and ruinous has been the impact generated in such cases. This phenomenon has justified the discussion about the necessity that the magistrate ponder about the potential effects of his/her decisions before pronouncing them, and, in this sense, the civil legislation has provided for such duty. Many relevant efforts have been taken by the Judiciary Power to reflect on the effects of judges’ decisions before taking them, without offending the law, the existing jurisprudence, precedents and constitutional principles, aiming at assertiveness, and especially at the efficiency of its manifestations, and, therefore, the efficiency of the very jurisdiction from a perspective of sustainability of the system of distribution of justice. Nevertheless, frequently there have been ultimate arguments grounding decisions that dismiss the law, and this, according to critics, implies unacceptable subordination of what is a priori right and good to mere considerations and consequentialist calculations. One can notice that opponents do not distinguish between these two modes of decision, by deeming them as consequentialist through a negativistic perspective. The main goal of the present study is to investigate whether, from the ethical-philosophical point of view, there can be good and bad consequentialism and whether there is the possibility that judicial consequentialist decisions can be made without violating the rules and principles that structure the legal system. For such an investigation the deductive method with qualitative exploratory research has been used along with a bibliographical survey and a case study. In the light of the findings, the conclusion was that there is the possibility of misuse of judicial consequentialism, in view of the absence of normative criteria for the justification of a decision which considers its potential consequences, the uncertainty about the reliability concerning the magistrate’s prognosis, and mechanisms to stabilize normative criteria to prevent such consequentialism from becoming a mere expedient to justify decisions without clear criteria and subordinated to interests disassociated from an adequate sense of justice. On the other hand, despite the efforts indicated in the first ascertainment, it is possible to notice that the term consequentialism has become polysemous, inducing errors of perception grounding criticism that does not take into account the effective possibility that the magistrate may have – by making use of the traditional hermeneutics and elements of other areas of knowledge, without any disregard for the law or the constitutional principles and norms – of extracting from the legal system alternative solutions in such a way that a consideration of the potential consequences of each alternative can be used as a methodological support to such Magistrate in the moment of decision neither doing any harm to the common good nor showing subordination of justice to lesser moral foundations, and, therefore, not necessarily showing any conceptual tension between a democratic rule-of-law state and consequentialism.